THE IMPORTANCE OF DEVELOPING PRIMARY STUDENTS' INTEREST IN LEARNING AND SKILLS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the development of interest in learning and skills of primary school students. Introduction, Formation of interest in learning in students, Development of learning skills, Use of innovative and modern methods, Parent-teacher cooperation, Taking into account the personal approach of students, Scientific point of view and practical examples, Practical examples, Statistical data, The role of modern approaches, Pedagogical recommendations, Conclusion, List of references.